A unique record of the Late Cretaceous of East-Central Europe: The first fossil wasps (Hymenoptera: Bethylidae, Spathiopterygidae) from the ajkaite amber (Bakony Mts., western Hungary). (November 2022) - Szabó, Márton; Brazidec, Manuel; Perrichot, Vincent; Szenti, Imre; Kukovecz, Ákos; Ősi, Attila
Abstract: The recently re-discovered, unique amber named ajkaite, coming from the Late Cretaceous (Santonian) Ajka Coal Formation is an unexpectedly rich source of arthropod inclusions. The present paper describes three new species of wasps from ajkaite, namely Ajkanesia harmincipsziloni Szabó & Brazidec gen. et sp. nov. (Bethylidae: Pristocerinae), Amissidigitus bela e Szabó & Brazidec gen. et sp. nov. (Bethylidae: Scleroderminae) and Spathiopteryx soosi Szabó, Brazidec & Perrichot sp. nov. (Spathiopterygidae). Hymenopterans were already reported from the Miocene and Pliocene of Hungary as adpression fossils, but these have only remained identified at higher taxonomical rank. Therefore, the three new ajkaite taxa are the first formally described fossil hymenopteran species from Hungary. The three ajkaite wasps greatly improve our knowledge on the Cretaceous fossil record of their respective (sub)families, which is otherwise very poorly documented. The suggested paleoenvironmental preferences of the new hymenopteran taxa accord with the forested, swampy to lacustrine ecosystem, in which the Ajka Coal has been deposited. Further ajkaite hymenopterans are likely to be stored in Hungarian museum collections. Highlights: Ajkanesia harmincipsziloni gen. et sp. nov., Amissidigitus belae gen. et sp. nov. and Spathiopteryx soosi sp. nov. are described. The species Aj . harmincipsziloni gen. et sp. nov. and Am . bela e gen. et sp. nov. both represent the second data of their subfamily from the Santonian. The Spathiopterygidae became extinct later in the Cretaceous than previously assumed.